CHANGE LEADERSHIP MODEL IN THE BOOK OF NEHEMIAH: A THEOLOGICAL ANALYSIS AND ITS IMPLICATIONS FOR CONTEMPORARY ORGANIZATIONAL MANAGEMENT - Benediktus James Widya Darmaka; Drisandri Bidrawati Mooy; Slamet Heriyanto; Dwi Aster Aviani (STT Bethel Indonesia Jakarta, 2026)
This study explores the leadership concepts demonstrated by Nehemiah in the context of the restoration of Jerusalem's walls. The primary focus is on the managerial strategies adopted by Nehemiah and how these principles can be applied in modern management contexts. By highlighting communication skills, decision-making, and collaboration, this article aims to provide new insights for business and organizational leaders. The methodology employed includes hermeneutic analysis and literature review, analyzing Nehemiah's leadership through scriptural texts and historical contexts. The findings reveal that Nehemiah's strategic approach to leadership can significantly enhance contemporary management practices. The novelty of this research lies in its application of ancient biblical principles to modern organizational challenges, offering a unique perspective on effective leadership.